Understanding and monitoring the capacitance‐voltage technique for the characterization of tandem solar cells. (13th January 2020) - Leon, Cyril; Le Gall, Sylvain; Gueunier‐Farret, Marie‐Estelle; Brézard‐Oudot, Aurore; Jaffre, Alexandre; Moron, Nicolas; Vauche, Laura; Medjoubi, Karim; Veinberg Vidal, Elias; Longeaud, Christophe; Kleider, Jean‐Paul
Abstract: This paper presents a simple and nondestructive method to determine doping densities and built‐in potential of subcells by adapting the well‐known capacitance‐voltage ( C ‐ V ) technique to two‐terminal (2 T) tandem solar cells. Because of the electrical coupling between the two subcells in a monolithic 2 T tandem solar cell, the standard method using a Mott‐Schottky plot (1/ C 2 vs V ) cannot be applied. Using numerical modeling, it is demonstrated that, by under chosen illumination conditions where only one subcell can absorb the light, it is possible to explore the bias dependence of the capacitance and to extract the parameters of the other subcell if the appropriate frequency conditions are present. This method is experimentally applied to an AlGaAs/Si tandem cell, and parameters of both AlGaAs and Si cells are extracted. Finally, the validity of that method is assessed by the very good agreement obtained when comparing the values extracted from our measurements on the tandem cell to those extracted from measurements on isotype cells and to the values targeted during the fabrication process of the AlGaAs/Si tandem solar cell. Abstract : Using analytical and numerical modeling approaches, a comprehensive analysis of the capacitance response of the tandem solar cell is developed. From there, despite the electrical coupling, parameters of the two subcells in an AlGaAs/Si monolithic tandem solar cell are accessed from capacitance‐voltage characterization under specific light bias. The good agreement between modeling, measurements, and the parameters targeted during the fabrication process validates the proposed method.